Incentivizing Antibiotic Research and Development - Leah Scandlen-Finken; Albert Wertheimer (University of Minnesota Libraries Publishing, 2015)
Antibiotic Resistance is an international threat, killing thousands and infecting millions. Although certain populations may be at an increased risk for infections, anyone can find themselves compromised with a multi-drug resistant infection. Treatments are becoming more complicated as the bacteria becomes more elusive. Cures are becoming less certain, and the future antibiotic arsenal is looking thin. Although there are many talented scientists and capable drug development entities, the funding and returns on investment are not sufficient to entice antibiotic research and development. This paper explores the current situation regarding antibiotic resistance and its casualties, as well as the mechanisms being employed to overcome the increase in resistance, and decrease in antibiotic effectiveness. Through analysis of antibiotic research, development, and regulation, this paper adds to the discussion by filling in the current gaps regarding the procurement of sustainable funding via an insurance model framework. By incentivizing the pharmaceutical industry to invest in antibiotic research, and by guaranteeing returns on investment, a global solution to the current antibiotic resistance problem can be contained.   Type: Student Project